INTERPRETASI SYUKUR DALAM ADAT ISTIADAT BABARIT MENURUT AL-QUR’AN SURAH IBRAHIM AYAT 7 - Nur Aminah NST; Nurmala Sari (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
This paper discusses the meaning of gratitude in the Qur'an in the Babarit Tradition in Kuningan. This study uses the history-social approach method, the results of the study show that the value of gratitude contained in the Koran is very broad in meaning, not limited to just an application when you get pleasure alone, but all aspects of life that are felt at that time. is a form to be grateful for. From the other side, in applying a form of gratitude to the Babarit tradition in Kuningan, there is a uniqueness, namely Babarit is an implementation of gratitude which is packaged in the routine activities of the Sundanese community which then has cultural values ​​as a Sundanese ethnic identity and also as a selling point for tourism attraction. in Kuningan.